Overt Subject Pronoun Use in Switch-Reference Contexts in Child Spanish Developmental Language Disorder: A Discriminant Function Analysis. - Dickinson, Kendra V.; Ortiz-Ramírez, Pedro Antonio; Arrieta-Zamudio, Ana; Grinstead, John; Flores-Ávalos, Blanca (Journal of Speech, Language & Hearing Research, 2023)
Purpose: Our study analyzes probabilistic constraints on subject expression previously found in adult Spanish in the speech of typically developing (TD) Spanish-speaking children and children with developmental language disorder (DLD). Previous work shows that children with DLD produce fewer overt subjects than typically developing children, and that the latter acquire constraints on subject expression as they age into adolescence. Our study complements these findings and provides further substance to the grammatical profile of children whose morphosyntactic development diverges from that of typically developing children. Method: Data are drawn from unstructured spontaneous production data from a sample of 19 monolingual Mexican, Spanish-speaking children, collected in 2006-2007. This sample includes 19 children diagnosed with DLD and 19 agematched, typically developing children. We collected all instances of finite verbs that either did or could have occurred with a subject personal pronoun uttered by the child participants and coded them for several factors including tense-mood-aspect, switch reference, and person and number. Results: We find that children with DLD produce fewer overt subject pronouns in switch reference contexts than typically developing controls, with a significant interaction of group and switch reference. Furthermore, a discriminant function analysis shows that overt pronoun use in switch reference contexts can form part of a useful diagnostic discriminant function, with high levels of sensitivity and specificity. Conclusions: Overall, we find important differences between TD Spanishspeaking children and those diagnosed with DLD regarding rates of overt subjects and sensitivity to the probabilistic constraint of switch reference. This finding contributes to our understanding of the morphosyntactic profiles of children with DLD, as well as the utility of factors such as switch reference in the identification of language disorders.